The Role of β-Fibrinogen Genotype in Determining Plasma Fibrinogen Levels in Young Survivors of Myocardial Infarction and Healthy Controls from Sweden - Green, Fiona; Hamsten, Anders; Blombäck, Margareta; Humphries, Steve (Thrombosis and Haemostasis, 1993)
β-fibrinogen G/A-455 polymorphism genotype was determined in 123 young survivors of myocardial infarction and 86 healthy controls from Sweden. Frequency of the A-455 allele was 0.25 (95% Confidence Interval 0.21–0.29) in both patients and controls, significantly higher than that reported previously (0.19, 95% Cl 0.16–0.22) in 292 men from the UK (1). Mean plasma fibrinogen level was significantly higher in patients (3.6 g/1) than in controls (3.1 g/1), with p <0.001. Genotype was significantly associated with (adjusted) plasma fibrinogen level in controls (p = 0.003). This effect was confined to the smokers (n = 50) where mean fibrinogen level was significantly (p = 0.001) higher in G/A-455 and A/A-455 individuals (3.5 g/1) compared with G/G-455 homozygotes (2.9 g/1). There was a significant interaction between smoking status and genotype in determining plasma fibrinogen levels in the controls. These data provide independent confirmation of the association between β-fibrinogen G/A-455 genotype and plasma fibrinogen levels previously observed in healthy men from the UK (1).